Is C1-C2 Reduction and Fixation A Good Choice in the Treatment of Recurrent Chiari-Like Symptoms With Syringomyelia? - HARMAN, FERHAT (ELSEVIER SCIENCE INC, 2021)
BACKGROUND: Foramen magnum decompression (FMD) is the first-choice treatment for Chiari malformation (CM). However, it has been suggested that cerebellar herniation and syringomyelia occur as a natural protective event to prevent neural damage caused by atlantoaxial instability. It is argued that treating instability is the main treatment. Positive results of atlantoaxial fusion have been reported in the literature, but there are no studies including the results of atlantoaxial fusion as the second treatment in patients in whom classical decompression failed. In our study, we report the results of these patients to help in the selection of treatment and we present our treatment algorithm for CM with syringomyelia. - METHODS: Thirteen patients who had undergone FMD and duraplasty due to CM and syringomyelia in our clinics and who had recovered clinically and radiologically but had recurrent complaints during long-term follow-up were evaluated. C1-C2 distraction and fusion were performed. We evaluated these patients radiologically and clinically. RESULTS: The mean age of the 13 patients was found to be 32.4 years. Male to female ratio was 6:7. The complaints recurred after an average of 2.1 years. Also, 3 cases were presented with their clinical characteristics and radiologic findings. CONCLUSIONS: FMD may fail even with duraplasty, and treatment of CM in recurrent cases is still controversial. Recently, atlantoaxial instability has been reported to be the main pathology of CM, and the cure for pathology is to treat instability. Recurrent CMs with syringomyelia in which FMD has failed should be treated by atlantoaxial fixation.
Keywords: C1-C2 fusion; Chiari malformation (CM); Posterior decompression; Reoperation